Pengaruh Pembelajaran Microteaching, Komunikasi Interpersonal, dan Teaching Skills Accounting Terhadap Keberhasilan PLP dengan Efikasi Diri Sebagai Variabel Mediasi - Rina Sella Arisyah; Rochmawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study was conducted with the aim of determining the effect of microteaching learning, interpersonal communication, and teaching skills accounting on the success of PLP (School Field Introduction) and investigating the indirect effect through the mediating variable, namely self-efficacy in Accounting Education students, class of 2021, Surabaya State University, totaling 70 students. This study is included in causal associative research with a quantitative approach. This study uses a saturated sample technique and is processed in SPSS 22 software. This study uses two types of data, namely primary and secondary. Primary data were obtained from the distribution of questionnaires to students, while secondary data were obtained through documentation of Microteaching and PLP course grades for Accounting Education students, class of 2021, Surabaya State University. The results of this study indicate that: 1) there is a positive and significant effect between Microteaching Learning (X1) on Self-Efficacy (Z). 2) there is a negative and significant effect between Interpersonal Communication (X2) on Self-Efficacy (Z). 3) there is a positive and significant effect between Teaching Skills Accounting (X3) on Self-Efficacy (Z). 4) there is a positive and significant influence between Microteaching Learning (X1) on the Success of PLP (Y). 5) there is a positive and significant influence between Interpersonal Communication (X2) on the Success of PLP (Y). 6) there is a negative and significant influence between Teaching Skills Accounting (X3) on the Success of PLP (Y). 7) there is a positive and significant influence between Self-Efficacy (Z) on the Success of PLP (Y). 8) Self-Efficacy (Z) is less able to mediate the influence of Microteaching Learning (X1) on the Success of PLP (Y) or semi-intervening. 9) Self-Efficacy (Z) is less able to mediate the influence of Interpersonal Communication (X2) on the Success of PLP (Y) or semi-intervening. 10) Self-Efficacy (Z) is able to mediate the influence of Teaching Skills Accounting (X3) on the Success of PLP (Y).